Efeito inibitório de óleos essenciais contra staphylococcus aureus multirresistentes e formadores de biofilmes - Benincá, Maisa Cristina (2018)
Staphylococcus aureus is one of the major pathogens responsible for foodborne diseases and is a public health problem in both industries and households. Many outbreaks are caused by a lack of information on good food handling and conservation practices, with direct contact between handlers and products being one of the main routes of contamination. Industries have been using chemical additives to prevent microbial growth and increase product shelf life. However, microorganisms have been gaining resistance due to the exacerbated use of antimicrobials and additives. In addition, consumers are looking for safe, natural alternatives to their diet. Essential oils (OEs) of plants are being used extensively in the preservation of raw and processed foods, and as pharmaceuticals in the t reatment of infectious diseases by alternative and natural medicine. The use of OEs is an alternative in the control of pathogenic bacteria, as it may present bactericidal action. In this work the in vitro inhibitory effect of the essential oils of Origanum compactum (Oregano), Cinnamomum cassia (cinnamon), Eugenia caryophyllus (clove), Thymus vulgaris L. (thyme) and Zingiber officinale Roscoe (ginger), compared to isolates of Staphylococcus aureus. The OEs of oregano and thyme presented better action, with the greater inhibition halos (p <0.05). In this way, the oils of Origanum vulgare and Thymus vulgaris L. were selected to evaluate the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) on five S. aureus isolates, considered susceptible in the agar diffusion test. In both tests, the two OEs showed MIC and MBC of 7,8 mg / mL (1: 128 dilution) for all isolates. With this study it was verified that the essential oils have an inhibitory effect on S. aureus, being an alternative of natural additive in the microbiological control to be used in food technology.